Ancient genomes from the last three millennia support multiple human dispersals into Wallacea - Oliveira, Sandra; Nägele, Kathrin; Carlhoff, Selina; Pugach, Irina; Koesbardiati, Toetik; Hübner, Alexander; Meyer, Matthias; Oktaviana, Adhi Agus; Takenaka, Masami; Katagiri, Chiaki; Murti, Delta Bayu; Putri, Rizky Sugianto; et al. (Springer, 2022)
Previous research indicates that human genetic diversity in Wallacea—islands in present-day Eastern Indonesia and Timor-Leste that were never part of the Sunda or Sahul continental shelves—has been shaped by complex interactions between migrating Austronesian farmers and indigenous hunter–gatherer communities. Yet, inferences based on present-day groups proved insufficient to disentangle this region’s demographic movements and admixture timings. Here, we investigate the spatio-temporal patterns of variation in Wallacea based on genome-wide data from 16 ancient individuals (2600–250 years BP) from the North Moluccas, Sulawesi and East Nusa Tenggara. While ancestry in the northern islands primarily reflects contact between Austronesian- and Papuan-related groups, ancestry in the southern islands reveals additional contributions from Mainland Southeast Asia that seem to predate the arrival of Austronesians. Admixture time estimates further support multiple and/or continuous admixture involving Papuan- and Asian-related groups throughout Wallacea. Our results clarify previously debated times of admixture and suggest that the Neolithic dispersals into Island Southeast Asia are associated with the spread of multiple genetic ancestries.